(untitled) (Fiep Bulletin - online, 2011)
The study aimed to compare the level of motor performance and the level of adiposity in female children and adolescent in schools from the city of Rio de Janeiro. A sample of 91 girls (12.3 ± 1.48 years) aged 10 to 15 years, belonging to public and private schools during Physical Education classes through the prior authorization of those responsible, by signing the informed consent form. The study was approved by the Ethics Committee of HUCFF/UFRJ. Body composition was estimated using anthropometric (ISAK, 2001), from measurements of skinfold thickness, height and total body mass and body fat percentage calculated according to the protocol proposed by Slaughter (1988) and classified by Lohman (1987). The motor tests performed up the proposal of Eurofit (MARINS & Giannichi, 2003). In results were used Kolgomorov Smirnoff test to verify the data distribution and the t-Student’s test was used for the comparison group, since it was established normality of the variables (SPSS 13.0, p≤0.05). It was found that girls classified as normal weight presented results of motor performance more impressive when compared to the group of overweight/obesity, and this comparison was statistically significant in most part of the tests.